Directive Speech Act in The Movie “Sleeping Beauty” - Muhartoyo Muhartoyo; Keilly Kristani (Bina Nusantara University, 2013)
Pragmatics is one of linguistics studies that is quite attractive to learn more about. There are many aspects of pragmatics; one of them is dealing with speech acts. Speech acts consist of many categories; one of them is directive speech act. This study aims to identify the directive speech act performed in “Sleeping Beauty” movie. Likewise, it will find out how often the directive speech act performed and which type of directive speech act that are most frequently used in the movie. This study used qualitative method in which data collection is done by watching the movie, analyzing the body movement and the dialogues of each character, reading the script and library research. A total of 139 directive speech acts were successfully identified. The result of analysis showed that the directive speech act of ordering is the most frequently used in the movie (21,6%). The least frequently used directive speech act is inviting directive speech act (0,7%). The study also revealed the importance of directive speech act in keeping the flow of storyline of the movie. This study is expected to give some useful insights in understanding what directive speech acts is.